Influence of radiolytic‐produced hydrogen peroxide on the stability of commercial kit 99mtechnetium‐exametazime preparation. (10th September 2013) - Martinez, Teresa; Miñana, Elena; Martín‐Falquina, Tomás Chivato; Fuente, Teodomiro
<x xml:space="preserve">Abstract</x> 99mTc‐d, l‐hexamethylpropylene amine oxime (99mTc‐d, l‐HMPAO) is a widely used radiopharmaceutical that suffers from an inherent instability with a shelf life of 30 min that constrains its availability for clinical use. A protocol for improving the stability of the kit with minimal modification of manufacturer's instructions and no chemicals addition to the commercial formulation is proposed. The protocol is based on the displacement of the oxygen present in the preparation, preventing free radicals build up and free pertechnetate formation. Although the degradation of 99mTc‐d, l‐HMPAO cannot be explained solely by the radiolytic production of free radicals, it appears to be an important factor in the shelf stability of the complex. Copyright © 2013 John Wiley & Sons, Ltd.